Interação nitrogênio e enxofre na produção e qualidade pós-colheita do tomateiro - Siueia Júnior, Matias (2017)
The consumption of vegetable is in constant growth, having the solanáceas, mainly the tomato, place of prominence. The tomato can be used both in natura and agroindustry, so it is important to take into consideration the quality of the fruit and its shelf life. Among the points that can influence these characteristics is the nutrition of the plant. The objective of this work was to evaluate combinations of nitrogen and sulfur rates on the nutrition, production and postharvest qualities of tomato. As a substrate, the dystroferric Red Latosol (LVdf) was used, in which three rates of sulfur (0, 60 and 120 mg dm -3 ) applied in the form of calcium sulfate and five rates of nitrogen (0, 100, 200, 300 and 400 mg dm -3 ) as urea labeled with 15 N, in a 3x5 factorial scheme, in a completely randomized design, under greenhouse conditions. The following evaluations were performed: fruit production, leaf contents N and S, titratable acidity, soluble solids, vitamin C content, and carotenoid pigments. The total production, dry shoot mass, N content and accumulation, as well as the SPAD index, increased as a function of N rates. The interaction between the N and S rates positively influenced the variables: firmness of the fruit, soluble solids, acidity and the SS / AT ratio, but negatively for the vitamin C, lycopene and β - carotene content, although it did not alter the fruit quality characteristics of the tomato in relation to the recommended values, in relation to the pH was only influenced by the inc reasing doses of N, reaching a maximum of 4.2 that resulted in fruits with a recommendable acidity degree. The rate of S that provided the greatest by fertilizer N utilization by the tomato was 120 mg dm -3 with 36.47%. Absorption of N tomato responded positively to S rate, reaching maximum absorption at the maximum dose of 400 mg dm -3 of N. The N/S ratio presented better response to the rate 60 mg dm-3 of S.